Preparation and Characterization of Poly(Methyl Methacrylate)/Clay and Poly(Methyl Acrylate)/Clay Nanocomposites by Microwave Irradiation And Conventional Heating - Yeoh, Ean Nee (2006)
Poly(methyl methacrylate)/clay and poly(methy acrylate)/clay nanocomposites are prepared by polymerizing the monomers in the presence of modified sodium montmorillonite (Na-MMT).Na-MMT is modified by either cetyltrimethylammonium(CTA+) or dodecylammonium (DDA+) ions via a cation exchange process. After the modification, CHN elemental analysis shows that CTA+ and DDA+ ions are present in the montmorillonite. Fourier Transform Infrared (FT-IR) spectra of CTA-MMT and DDA-MMT clearly indicate the presence of new absorption bands, i.e. C-H asymmetric and symmetric stretching vibrations. The basal spacing of CTA-MMT and DDA-MMT increases from 11.6Å to 19.3Å and 18.7Å, respectively.Thermal gravimetric analysis(TGA) shows that CTA-MMT and DDA-MMT degrade at higher temperatures as compared to Na-MMT. Conversions of methyl methacrylate (MMA) and methyl acrylate (MA) into the polymers are carried out by either microwave irradiation or conventional heating methods in the presence of benzoyl peroxide as the initiator.The microwave assisted preparation of PMMA/clay and PMA/clay nanocomposites significantly reduces the reaction period as compared to conventional heating.Gel permeation chromatography (GPC) results show that polydispersity indices of PMMAs prepared at high (650 W) and medium high (530 W) microwave power level and PMAs prepared at high microwave power level are narrower than that of PMMA and PMA prepared by conventional heating. FT-IR spectra of PMMA/clay and PMA/clay clearly indicate the presence of the polymer and clay functional groups. X-ray diffraction analysis (XRD) analysis shows that there are increments in the clay basal spacing of the PMMA/clay and PMA/clay nanocomposites prepared by both methods. This indicates that PMMA or PMA are successfully intercalated into the interlayer galleries of the clay.However, transmission electron microscopy (TEM) shows that the nanocomposites are of intercalated and flocculated type. The TGA thermograms indicate enhancement in thermal stability for PMMA/clay and PMA/clay nanocomposites and microcomposites as compared to that of the pure PMMA or PMA prepared by both microwave irradiation and conventional heating. The remarkable improvement in storage modulus of PMMA/clay and PMA/clay nanocomposites compared to that of the pure PMMA and PMA indicates there is a strong interaction between the matrix and the organoclay. The glass transition temperatures (Tg) of PMMA/CTA-MMT nanocomposites increase by around 10-20 oC as compared to that of the pure PMMA. PMMA/DDA-MMT nanocomposite with 1 wt% of DDA-MMT filled PMMA gives a higher Tg compared to the other DDA-MMT filled PMMA.However, the Tg for PMA/CTA-MMT and PMA/DDA-MMT nanocomposites is similar to that of the pure PMA